Pengaruh Kepemimpinan Lingkungan Kerja dan Kompensasi Terhadap Loyalitas Kerja Karyawan di PT. Bali Kulina Utama - Ni Made, Wina Novriani; Ni Made, Yudhaningsih; I Nyoman, Gede Supraptha (ManBiz: Journal of Management and Business, 2024)
This study investigates the phenomenon of low turnover rates at PT Bali Kulina Utama, despite deficiencies in recognition, rewards, and career development opportunities. The study aims to analyze the impact of leadership style, work environment, and compensation on employee loyalty, and to explore the combined effect of these factors on employee retention at the company. The research employs a quantitative approach with a sample size of 58 employees from PT Bali Kulina Utama. Data collection is conducted using a questionnaire, and measurement is based on a Likert scale. Data analysis involves descriptive statistics, multiple linear regression, and hypothesis testing, with data processed using SPSS 27 for Windows. The results of the t-test indicate that the Leadership Style variable has a significance value of 0.0446, which is less than 0.05, suggesting that Leadership Style has a positive and significant effect on employee loyalty at PT Bali Kulina Utama. The Work Environment variable has a significance value of 0.040, also less than 0.05, indicating a positive and significant impact on employee loyalty. The Compensation variable has a significance value of 0.043, which is less than 0.05, demonstrating a positive and significant influence on employee loyalty. The F-test results show an Fvalue of 5.531 with a significance level of 0.012, indicating a positive and significant impact of Leadership Style, Work Environment, and Compensation on employee loyalty at PT Bali Kulina Utama.